The utilization of Jackfruit seed flour (Artocarpus heteropyllus) as substitution of rice bran in rations on Kampung chicken performances - Jekson Pasaribu; Edhy Mirwandhono; Sayed Umar; Hamdan .; Nevy Diana Hanafi (Universitas Sumatera Utara, 2017)
Abstract. The objective of this research is analyze the extent to which the utilization of jackfruit seed flour can substitute rice bran in rations on the performance of chicken. This research was conducted in laboratory of livestock breeding livestock study program of agricultural faculty of north sumatera university, in March-April 2017. The design used in this research is randomized block design (RAK) with 4 treatments and 3 groups. Treatment with various levels of jackfruit seed meal ration with P0 (0%), P1 (10%), P2 (20%), P3 (30%). The parameters in this study are ration consumption, weight gain and ration conversion.The results showed the average consumption (g / head / day) for treatment P0; P1; P2; P3 of; 349,53; 345,71; 354.28; 343.67, then weight gain (PBB) (g / head / day) were; 98,85; 100,41; 92.49; 100.8, and ration conversion of; 6.36; 6.28; 6.87 and 6.21. The results of the diversity analysis showed that the utilization of Jackfruit seed flour gave no significant effect (P> 0,05) on the performance of chicken. The conclusion of this research is the use of jackfruit seed flour in ration can substitute rice bran in chicken ration.